Sleep Disturbances and Autonomic Dysfunction in Patients with Postural Orthostatic Tachycardia Syndrome - Mallien, Julia; Isenmann, Stefan; Mrazek, Anne; Haensch, Carl-Albrecht (Frontiers in Neurology, 2014)
Many patients with Postural Tachycardia Syndrome (PoTS) suffer from fatigue, daytime sleepiness and sleeping disturbances. The objective of this study was to compare subjective and objective sleep quality of PoTS patients with a group of healthy controls. All Patients completed a Pittsburgh Sleep Quality Index questionnaire and the Epworth Sleepiness Scale. The patients sleep architecture, heart rate and heart rate variability measurements were taken during one night at the sleep laboratorium. All Data was collected at the Sleep Unit, at Helios Klinikum Wuppertal. 38 patients diagnosed with PoTS were compared to 31 healthy controls, matched in age and gender. Patients with PoTS reached significantly higher scores in sleep questionnaires, which means that they were more sleepy and had a lower sleep qualitiy. Polysomnography showed a significantly higher proportion of stage 2 sleep. The results of heart rate variability analysis in different sleep stages confirmed changes in autonomic activity in both groups. PoTS patients, however, showed a diminished variability of the LF band, HF band and LF/HF ratio in different sleep stages. It can therefore be gathererd that PoTS could be considered as potential differential diagnosis for sleep disturbances since PoTS patients had a subjective diminished sleep quality, reached higher levels of daytime sleepiness and showed a higher proportion of stage 2 sleep. PoTS patients showed furthermore a reduction of LF/HF ratio variability in different sleep stages.